PENGARUH DUKUNGAN SOSIAL KELUARGA DAN EFIKASI DIRI TERHADAP PENGAMBILAN KEPUTUSAN KARIER SISWA KELAS XI SMKN 40 JAKARTA - Muhammad Rizkya Aziz; Christian Wiradendi Wolor; Eka Dewi Utari (STKIP Subang, 2026)
This study examined the statistical effects of family social support and self-efficacy on career decision-making among Grade XI students at SMKN 40 Jakarta. The study addressed students’ uncertainty in selecting work, higher education, training, or entrepreneurship pathways after graduation. A quantitative explanatory approach with a cross-sectional survey design was employed. All 215 students in the accessible population were included through census sampling. Data were collected using four-point Likert questionnaires comprising 16 items of family social support, 20 items of self-efficacy, and 10 items of career decision-making, then analyzed using multiple linear regression in JASP 0.19.1.0. All 46 items were valid, and the three instruments were reliable, with Cronbach’s alpha values of 0.866, 0.891, and 0.772. Family social support had a positive and significant statistical effect on career decision-making (b = 0.186; β = 0.296; t = 4.714; p < 0.001). Self-efficacy also had a positive and significant effect (b = 0.167; β = 0.331; t = 5.275; p < 0.001). The simultaneous model was significant (F = 38.180; p < 0.001), with R² = 0.265 and adjusted R² = 0.258. Thus, both predictors explained 26.5% of the variance in career decision-making. The findings support the integration of family involvement and self-efficacy strengthening in vocational career guidance, while the cross-sectional design limits causal interpretation.